The 21 irrefutable laws of leadership workbook follow them and people will follow you - Maxwell, John C (Thomas Nelson, 2007)
What would happen if a top expert with more than 40 years of leadership experience were willing to distill everything he had learned about leadership into a handful of life-changing principles just for you? It would change your life. John C. Maxwell has done exactly that in The 21 Irrefutable Laws of Leadership. He has combined insights learned from his thirty-plus years of leadership successes and mistakes with observations from the worlds of business, politics, sports, religion, and military conflict. The result is a revealing study of leadership delivered as only a communicator like Maxwell can